Understanding methane flame kinetics from reduced mechanisms. (4th April 2007) - Skevis, G.; Goussis, D.A.; Mastorakos, E.
Reduced mechanisms for laminar premixed methaneair flames are constructed on the basis of the GRI-3.0 detailed chemistry. It is demonstrated that significant understanding of the flame chemistry can be acquired by examining reduced mechanisms generated on the basis of either the full flame domain or specific subdomains, such as the preheat, the flame and the post-flame zones. Reduced mechanisms of increasing number of steps generated by taking into account the full flame domain identify the parts of chemistry that relate to the slowest chemical time scales and thus dominate the overall flame structure. Observed differences in the reduced mechanisms of a given size generated on the basis of different regions of the flame distinguish the locally prevailing kinetic paths. The effects of inlet mixture composition on the dominant parts of chemistry are discussed.